O jazz e a mundialização: processos culturais e consumo musical no século XX - Ramelo, Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Jazz brings to the surface discussions about globalization and its unfolding. The development of such music style allows a reflection about the processes that influence 20th century culture, thus enabling a closer look into debates that involve cultural industrialization and standardization in such context. Horkheimer‟s and Adorno‟s work deal with this theme, considering culture as something standardized, a result of the process that fits into the industrial production mold. Morin goes further in this discussion, suggesting the emergence of a mass culture as a third culture. Later, Latin-American authors Ortiz and Canclini bring up new tones and approaches to the globalization through culture theme

O jazz traz à tona discussões acerca da globalização e seus desdobramentos. O desenvolvimento desse estilo musical permite uma reflexão dos processos que acometem a cultura no século XX, além de possibilitar um olhar mais atento aos debates que envolvem a padronização e a industrialização cultural neste contexto. As obras de Adorno e Horkheimer tratam dessa temática, tendo em vista a cultura enquanto algo padronizado, resultado do processo que se enquadra nos moldes da produção industrial. Morin avança nessa discussão, sugerindo a emergência de uma cultura de massas enquanto uma terceira cultura. Posteriormente, os autores latino-americanos Ortiz e Canclini imprimem novos tons e abordagens para o tema da globalização pensada através da cultura
Keywords: Globalização; Cultura; Jazz; Música; Padronização; Globalization; Standardization; Culture